2012
DOI: 10.1016/j.neuropharm.2012.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The duration of nicotine withdrawal-associated deficits in contextual fear conditioning parallels changes in hippocampal high affinity nicotinic acetylcholine receptor upregulation

Abstract: A predominant symptom of nicotine withdrawal is cognitive deficits, yet understanding of the neural basis for these deficits is limited. Withdrawal from chronic nicotine disrupts contextual learning in mice and this deficit is mediated by direct effects of nicotine in the hippocampus. Chronic nicotine treatment upregulates nicotinic acetylcholine receptors (nAChR); however, it is unknown whether upregulation is related to the observed withdawal-induced cognitive deficits. If a relationship between altered lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

5
5

Authors

Journals

citations
Cited by 54 publications
(83 citation statements)
references
References 67 publications
4
79
0
Order By: Relevance
“…In addition to these general symptoms, cognitive deficits such as difficulty concentrating (Pomerleau et al 2000), disrupted working memory (Jacobsen et al 2005;Mendrek et al 2006), verbal memory problems (Jacobsen et al 2005), increased response time (Snyder et al 1989;Bell et al 1999), and problems in paired-associate learning (Kleinman et al 1973) were observed during nicotine withdrawal. In line with these reports, animal studies also showed that while chronic nicotine did not have any effect on hippocampus-dependent contextual and trace fear conditioning, nicotine withdrawal impaired hippocampal learning and memory (Davis et al 2005;Davis and Gould 2009;Raybuck and Gould 2009;Gould et al 2012Gould et al , 2014aPortugal et al 2012a, b;. Overall, human and animal studies demonstrate hippocampus-dependent learning and memory enhancement during initial nicotine exposure and cognitive deficits during nicotine withdrawal.…”
Section: Nicotinementioning
confidence: 71%
“…In addition to these general symptoms, cognitive deficits such as difficulty concentrating (Pomerleau et al 2000), disrupted working memory (Jacobsen et al 2005;Mendrek et al 2006), verbal memory problems (Jacobsen et al 2005), increased response time (Snyder et al 1989;Bell et al 1999), and problems in paired-associate learning (Kleinman et al 1973) were observed during nicotine withdrawal. In line with these reports, animal studies also showed that while chronic nicotine did not have any effect on hippocampus-dependent contextual and trace fear conditioning, nicotine withdrawal impaired hippocampal learning and memory (Davis et al 2005;Davis and Gould 2009;Raybuck and Gould 2009;Gould et al 2012Gould et al , 2014aPortugal et al 2012a, b;. Overall, human and animal studies demonstrate hippocampus-dependent learning and memory enhancement during initial nicotine exposure and cognitive deficits during nicotine withdrawal.…”
Section: Nicotinementioning
confidence: 71%
“…Previous studies suggest that the upregulated pool of nAChRs arising from long-term exposure to nicotine may drive elements of the nicotine withdrawal syndrome (Turner et al, 2011;Gould et al, 2012), and this protracted upregulation of nAChRs has been correlated with reduced ability to maintain abstinence in the clinical population (Staley et al, 2006). Therefore, to determine whether ABT-089 reduced anxiety during nicotine withdrawal in the NIH via maintenance of upregulated nAChRs, we quantified [ 3 H]EB binding density after long-term ABT-089 administration during nicotine withdrawal.…”
Section: Anxiolytic Effects and Nachr Regulation Of Abt-089 Discussionmentioning
confidence: 99%
“…There is also evidence suggesting that during chronic nicotine administration, hippocampal nAChRs desensitize and upregulate and the resulting hypersensitive cholinergic system may be responsible for the effects of nicotine withdrawal on hippocampus-dependent learning (Dani & Heinemann, 1996; Gould et al, 2012; Marks, Grady, & Collins, 1993; Wilkinson & Gould, 2013). In support, Gould et al (2012) found that chronic nicotine increased nAChR binding in the hippocampus and the duration of nAChR upregulation paralleled the duration of withdrawal deficits in hippocampus-dependent learning. Also supporting the role of hypersensitive nAChRs in the withdrawal effects, Wilkinson and Gould (2013) found that reintroducing acute nicotine into the system during nicotine withdrawal lead to an even greater enhancement of the contextual fear conditioning compared to the effects of acute nicotine in previously nicotine naïve mice.…”
Section: Involvement Of Nachrs In Anxiety and Anxiety Disordersmentioning
confidence: 99%